2013
DOI: 10.1111/ejh.12134
|View full text |Cite
|
Sign up to set email alerts
|

Renal diseases in haemophilic patients: pathogenesis and clinical management

Abstract: Haemophilia A and B are genetic X-linked bleeding disorders, caused by mutations in genes encoding factors VIII and IX, respectively. Clinical manifestations of haemophilia are spontaneous haemorrhage or acute bleeding caused by minor trauma, resulting in severe functional consequences that can culminate in a debilitating arthropathy. Life expectancy and quality of life of patients with haemophilia have dramatically improved over the last years, mainly for new therapeutic options and the awareness to the risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
2
21
0
3
Order By: Relevance
“…These exciting advances changed the clinical history of these patients and revealed novel disease-or therapy-related problems including renal dysfunction [30,31]. Muscular dystrophies are among the most common single gene disorders with DMD being the most frequent form affecting 1 of 3500 to 6000 newborn males.…”
Section: Discussionmentioning
confidence: 99%
“…These exciting advances changed the clinical history of these patients and revealed novel disease-or therapy-related problems including renal dysfunction [30,31]. Muscular dystrophies are among the most common single gene disorders with DMD being the most frequent form affecting 1 of 3500 to 6000 newborn males.…”
Section: Discussionmentioning
confidence: 99%
“…Renal disease in hemophilia is rare and common causes are hypertension, diabetes, coronary artery disease, viral infections(HIV, hepatitis B & C),drug nephrotoxicity (antivirals, antibiotics, etc.) and kidney bleeding . Kulkarni et al reported the incidence of renal failure in hemophilia patients as 2.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal dialysis is a slightly better option in hemophiliacs according to available literature since there is no need for any additional replacement of factor VIII. However risk of intraperitoneal or retroperitoneal hemorrhage and malnutrition due to protein loss are still a concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations